- \(1^2+2^2+3^2+...10^2\)
- \(S=2^2+4^2+6^2+...+20^2\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = \(2^2.\left(1^2+2^2+3^2+...+10^2\right)=4.385=1540\)
B=\(3^2.\left(1^2+2^2+3^2+...+10^2\right)=385.9=3465\)
Ta có : \(1^2+2^2+3^2+......+10^2=385\)
\(2^2\left(1^2+2^2+3^2+......+10^2\right)=2^2.385\)
\(2^2+4^2+6^2+.....+20^2=4.385\)
\(2^2+4^2+6^2+.....+20^2=1540\)
S=22+42+62+...+202
S=(2*1)2+(2*2)2+(2*3)2+...+(2*10)2
=22*12+22*22+...+22*102=22(12+22+32+...+102)=4*385=1540
Vậy S=1540
\(S=2^2+4^2+....+20^2=?\)
\(=\left(2.1\right)^2+\left(2.2\right)^2+\left(2.3\right)^2+....+\left(2.10\right)^2\)
\(=2^2.1^2+2^2.2^2+2^2.2^3+...+2^2.10^2\)
\(=2^2.\left(1^2+2^2+3^2+...+10^2\right)\)
\(=2^2.385\)
\(=4.385\)
\(=1540\)
S=22+42+...+202
=> 1/2 .S=12+22+...+102
=> 1/2 .S=385
=> S = 385 . 2
=> S = 770
Ta có:
\(2^2\left(1^2+2^2+3^2+...+10^2\right)=2^2+4^2+6^2+...+20^2=S\)
=> \(S=2^2.385=1540\)
S = 2^2 + 4^2+6^2+.....+20^2
= ( 1.2 ) ^2 + ( 2.2)^2 +.....+ (2.10 ) ^2
= 2^2( 1^2 + 2^2 +.....+ 10^2 )
=2^2 . 385
= 4 . 385 = 1540
\(S=2^2+4^2+6^2+....+20^2\)
\(=\left(1.2\right)^2+\left(2.2\right)^2+\left(2.3\right)^2+...+\left(2.10\right)^2\)
\(=1^2.2^2+2^2.2^2+2^2.3^2+....+2^2.10^2\)
\(=2^2.\left(1^2+2^2+3^2+....+10^2\right)\)
Mà \(1^2+2^2+3^2+...+10^2=385\)
Nên \(S=2^2.385=4.385=1540\)
\(S=2^2+4^2+.....+20^2\)
\(S=1^2.2^2+2^2.2^2+.......+10^2.2^2\)
\(S=2^2.\left(1^2+2^2+.....+10^2\right)\)
\(S=4.385=1540\) (đề bài)
Đặt \(A=1^2+2^2+3^2+...+10^2=\left[1\cdot1\right]^2+\left[2\cdot1\right]^2+\left[3\cdot1\right]^2+...+\left[10\cdot1\right]^2\)
\(=1^2\cdot1^2+2^2\cdot1^2+3^2\cdot1^2+...+10^2\cdot1^2\)
\(=1^2\left[1^2+2^2+3^2+...+10^2\right]=1\cdot385=385\)
\(S=2^2+4^2+6^2+...+20^2\)
\(=\left[2\cdot1\right]^2+\left[2\cdot2\right]^2+\left[2\cdot3\right]^2+...+\left[2\cdot10\right]^2\)
\(=2^2\cdot1^2+2^2\cdot2^2+2^2\cdot3^2+...+2^2\cdot10^2\)
\(=2^2\left[1^2+2^2+3^2+...+10^2\right]=4\cdot385=1540\)